Happiness of economists - Lars P. Feld; Sarah Necker; Bruno S. Frey (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik, 2013)
This study investigates the determinants of economists' life satisfaction. The analysis is based on a survey of professional, mostly academic economists from European countries and beyond. We find that certain features of economists' professional situation influence their well-being. Happiness is increased by having more research time while the lack of a tenured position decreases satisfaction in particular if the contract expires in the near future or cannot be extended. Surprisingly, publication success has no effect on satisfaction. While the perceived level of external pressure also has no impact, the perceived change of pressure in recent years has. Economists may have accepted a high level of pressure when entering academia but do not seem to be willing to cope with the increase observed in recent years.
Keywords: I31; A11; J28; 330; happiness; academic labor market; extrinsic and intrinsic motivation; publish or perish-culture